2007
DOI: 10.1097/01.blo.0000238828.65434.b0
|View full text |Cite
|
Sign up to set email alerts
|

A Hydroxyapatite Graft Substitute Reduces Subsidence in a Femoral Impaction Grafting Model

Abstract: Synthetic bone graft substitutes have been developed for impaction grafting revision hip surgery in response to concerns about the availability and potential infection risk of allograft. We performed an in vitro experiment to determine whether a synthetic porous hydroxyapatite material might improve resistance to cumulative subsidence and cyclic (elastic) movement on loading. We impacted different ratios of hydroxyapatite and allograft (0%, 50%, 70%, and 90% hydroxyapatite) into composite femoral models (eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The distal migration of the Exeter™ stem relative to the Sawbones ® femurs was in line with other in vitro studies. In two recent studies similar to our experiment, Exeter™ stems were used in combination with the impaction grafting technique [ 30 , 44 ]. In one study, subsidence values of 0.44 mm and 0.13 mm were observed after 18,000 cycles for reconstructions with only bone chips and reconstructions that contained allografts and hydroxyapatite graft extenders, respectively [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distal migration of the Exeter™ stem relative to the Sawbones ® femurs was in line with other in vitro studies. In two recent studies similar to our experiment, Exeter™ stems were used in combination with the impaction grafting technique [ 30 , 44 ]. In one study, subsidence values of 0.44 mm and 0.13 mm were observed after 18,000 cycles for reconstructions with only bone chips and reconstructions that contained allografts and hydroxyapatite graft extenders, respectively [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In two recent studies similar to our experiment, Exeter™ stems were used in combination with the impaction grafting technique [ 30 , 44 ]. In one study, subsidence values of 0.44 mm and 0.13 mm were observed after 18,000 cycles for reconstructions with only bone chips and reconstructions that contained allografts and hydroxyapatite graft extenders, respectively [ 30 ]. The other study had subsidence values of 2.31 mm and 0.99 mm after 10,000 loading cycles for reconstructions with pure allografts and reconstructions with a mix of allografts and hydroxyapatite graft extenders, respectively [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stem subsidence can occur through failure of the cement and the graft at interfaces between these materials and the stem or cortex. Munro et al 14 performed an experiment in vitro to investigate whether increasing ratios of a synthetic porous HA material might also improve resistance to cumulative subsidence and cyclical movement on loading compared to 100% allograft in impaction grafting of the femur. Their results demonstrated that subsidence at the prosthesis-cement mantle and cyclical movement both significantly decreased with the addition of HA.…”
Section: Discussionmentioning
confidence: 99%
“…TCP/HA particles mixed with bone grafts showed better stability than bone grafts alone. Similar results of mechanical engineering testing as well as animal model were presented of femoral reconstructions with the use of TCP/HA bone graft substitutes [ 11 , 21 ]. The papers presenting outcomes of bone grafts substitutes used in bone stock reconstruction during revision hip arthroplasty differ in relation to the type of material used and include as follows: xenograft [ 22 , 23 ], glass ionomer ceramics [ 9 ], corraline derived hydroxyapatite [ 24 ], calcium sulphate [ 18 , 25 ], HA [ 7 , 26 28 ], TCP [ 7 , 29 ] and TCP/HA [ 10 , 30 34 ].…”
Section: Discussionmentioning
confidence: 58%
“…Biphasic granules of TCP/HA have pores whose size has been revealed to be optimal for osteoconduction. TCP/HA granules are manufactured in particulate form with harder consistency than morsellized allograft to withstand impaction grafting forces and enhance the initial stability of the implant [ 10 , 20 , 21 , 36 ]. TCP/HA particles are slowly replaced by host bone [ 34 ].…”
Section: Discussionmentioning
confidence: 99%